Food Waste and Dynamic Inconsistency: A Behavioral Economics Perspective - Alexander M. Danzer; Helen Zeidler (Institute of Labor Economics (IZA), 2025)
This paper examines the link between dynamically inconsistent time preferences and individual food waste behavior. Food waste is conceptualized as unintentional outcome of choices along the food consumption chain. Capitalizing on a nationally representative longitudinal survey from Germany, we construct targeted metrics of food consumption and waste behaviors. We find that more present-biased individuals waste more food. Our study investigates the behavioral mechanism that involves postponing domestic consumption of healthy food despite good consumption intentions, resulting in food spoilage. Studying inconsistencies between grocery shopping and food preparation is pivotal for understanding the significant, persistent amounts of food waste within households.
Keywords: D12; D15; Q53; Q18; 330; food waste; food consumption; dynamic inconsistency; healthy eating